El desarrollo sensorial fomentado por actividades táctiles y auditivas en los estudiantes de la Unidad Educativa Especializada de no Videntes Cotopaxi; ubicada en la parroquia La Matriz, cantón Latacunga, provincia Cotopaxi; en el año lectivo 2014 -2015 - Montaluisa Escobar, Martha Beatriz (2015)
The present research was an important topic for Cotopaxi Blind Educational Institution, according real conditions around authorities, teachers and students pedagogical, didactic and academic point of view, because active learning strategies and methods are not correctly applied to get better sensorial abilities and skills, improving an inclusive culture which one let the society advance by an equal instruction directed to an high quality education and specially for a good life style. Research objective was made in way to improve student’s senses, using activities focused to their disabilities with an adequate environment to maximize these activities. Other important factor was to transmit alternatives to the institution increasing teachers’ class room management. It was a field descriptive investigation; to decide the theme and collect some information different techniques were applied as, interview, inquest and observation sheet, getting the next conclusion; it is possible learning better implementing a tactile and audio manual.